Players' work time : a history of the British Musicians' Union, 1893-2013 - Williamson, John, 1949-; Cloonan, Martin (Manchester University Press, 2016)
This critical account of the Musicians' Union from 1893-2013 explores the organisation's development as a set of responses to technological, industrial and socio-political changes.